Transformers : analysis, design, and measurement - López-Fernández, Xose M.; Ertan, H. Bülent; Turowski, J. (CRC Press, 2013)
This book focuses on contemporary economic, design, diagnostics, and maintenance aspects of power, instrument, and high frequency transformers, which are critical to designers for a transformer stations. The text covers such topics as shell type and superconducting transformers as well as coreless PCB and planar transformers. It emphasizes challenges and strategies in transformer design and illustrates the importance of economics in transformers management by reviewing life cycle cost design and the use of decision methods to manage risk.